Electrical, Optical and Luminescent Properties of Zinc Oxide Single Crystals - Markevich, I. V.; Borkovska, L. V.; Venger, Ye. F.; Korsunska, N. O.; Kushnirenko, V. I.; Melnichuk, O. V.; Melnichuk, L. Yu.; Khomenkova, L. Yu. (Ukrainian Journal of Physics, 2018)
This review includes the results of investigations of the electrical, photoelectrical, optical, and luminescent properties of undoped single crystals of ZnO grown by the gas-cycle method. It is shown that the high conductivity of ZnO is caused by interstitial Zn atoms (Zni) that are shallow donors and are mobile at room temperature. It is found that the Zni relocation under intrinsic fields results in the appearance of the residual conductivity, shift of the optical absorption edge to longer wavelengths, and distortion of the exciton luminescence spectra. It is shown that the thin near-surface layer with high n-type conductivity arises due to the accumulation of Zni donors near the crystal surface due to their drift in the electric field of a depleted band caused by the oxygen adsorption. Based on the comparison of the exciton luminescence spectra and excitation spectra of the defect-related emission, it is proposed that the main excitation mechanism of the latter consists in the non-radiative recombination of excitons on the defect centers accompanied by the energy transfer to electrons located on these centers. The thermoluminescence of ZnO excited with the Joule heat release has been investigated. It is shown that this effect is caused by the recombination of equilibrium carriers produced by the heating through lattice defects.